Pregnancy-associated plasma protein A as an independent mortality predictor in long-term hemodialysis patients - Kalousová, Marta; Benáková, Hana; Kuběna, Aleš; Dusilová-Sulková, Sylvie; Tesař, Vladimír; Zima, Tomáš (Kidney & blood pressure research, 2012)
BACKGROUND/AIMS: Pregnancy-associated plasma protein A (PAPP-A) is a biomarker related to vascular damage. The aim of the study was to focus on PAPP-A and related parameters and their relationship to the prognosis of long-term hemodialysis (HD) patients. METHODS: This is a prospective observational cohort study which included 261 long-term HD patients followed up for 5 years and 66 healthy subjects. PAPP-A, placental growth factor (PlGF), matrix metalloproteinase 2 and 9 (MMP-2, MMP-9), insulin-like growth factor 1 (IGF-1), insulin-like growth factor binding protein-4 (IGFBP-4), and cardiac, nutritional and inflammatory parameters were measured at the beginning of the study and tested as predictors of mortality. RESULTS: PAPP-A, PlGF, IGF-1, IGFBP-4 and MMP-2 were significantly increased in HD patients compared to controls (PAPP-A 27.6 ± 15.5 mIU/l in HD vs. 9.4 ± 2.5 mIU/l in controls, p < 0.001). Increased PAPP-A was a significant independent predictor of overall mortality and mortality due to infection in the multivariate Cox analysis [HR (95% CI): 1.237 (1.060-1.444), p = 0.007, and 1.416 (1.115-1.798), p = 0.004, per standard deviation, respectively]. PAPP-A was not related to cardiovascular mortality. CONCLUSION: Increased PAPP-A is a significant independent predictor of overall mortality and mortality due to infection but it was not related to cardiovascular mortality in this study.
Keywords: Humans; lidé středního věku; Pregnancy-Associated Plasma Protein-A; kohortové studie; Predictive Value of Tests; Renal Dialysis; následné studie; Female; Aged; dialýza ledvin; senioři; lidé; Biomarkers; těhotenský plazmatický protein A; časové faktory; Cohort Studies; Survival Rate; biologické markery; ženské pohlaví; Male; Middle Aged; prediktivní hodnota testů; míra přežití; mužské pohlaví; prospektivní studie; Time Factors; Follow-Up Studies; Prospective Studies